Weighting analysis on air pollution among recent years in China via grey theory models - Chen, Wei-Ting; Chang, I-Chia; Li, Zhigang (Frontiers in Environmental Science, 2022)
The priority of national development has always been economic development during the recent decades in China, so a lot of energy consumption was needed to support rapid economic development, accompanied by a number of different air pollution emissions, including SO2, NO2 CO, and PM2.5. Based on awareness of environmental protection and sustainable energy development, researchers aimed to propose strategies to reduce the amount of air pollution generation in China derived from intense industrialization. The calculation of the correlation coefficient showed high values, so the correlation of air pollutants is highly related. This study aimed to realize the outcome of the implementation of air pollution reduction acts. Therefore, the grey relational grade and grey entropy were used to analyze the air pollution trend from 2013 to 2020 due to the specific function of the grey theory. The results of this study showed that the curves of SO2, PM2.5, and CO showed a clear decreasing trend. Furthermore, the SO2 curve still decreased in the periods of 2018–2020. The most important index for air pollutants is SO2 after the calculation of grey entropy, which corresponds to the fact that the coal resource is the main energy source in the fossil fuel industries for economic growth. However, the effects of these implementations regarding air pollution reduction sufficiently control air pollution emission, especially SO2 emission.